Science unites a troubled world: Lessons from the pandemic - Booz, George W. (Eur J Pharmacol, 2021)
European Journal of Pharmacology has published a special issue entitled Therapeutic targets and pharmacological treatment of COVID-19 that contains more than 30 manuscripts. Scientists from around the world contributed both review articles and original manuscripts that are remarkable in their diversity. Each contribution offers a unique perspective on the current approaches of the discipline called pharmacology. Yet the contributions share an enthusiasm to put forward a fresh viewpoint and make a positive difference by the exchange of ideas during the troubled times of this pandemic. What other enterprise but science can unite so many diverse cultures and nationalities in global uncertainty and discord, and mobilize an effective response against a common enemy. The efforts of science are in stark contrast to those of populism that has introduced division and a self-serving attitude that are not simply ill-matched to tackle the pandemic, but foster its spread and severity. We trust that the readers of European Journal of Pharmacology will discover new ideas and concepts in our special COVID-19 series as members of the scientific community and shared world.